Penerapan Sistem Pendukung Keputusan Dengan Metode Profile Matching untuk Menentukan Mahasiswa Berprestasi (Studi Kasus di Poltekkes Kemenkes Padang) - Kamelia Sari, Rima; Defit, Sardjon; Widi Nurcahyo, Gunadi (RJOCS (Riau Journal of Computer Science), 2023)
The Health Polytechnic of the Ministry of Health of Padang annually conducts selection activities for outstanding students. The process of selecting outstanding students at the Health Polytechnic of the Ministry of Health in Padang is still done manually, therefore to determine outstanding students it is necessary to design a computerized Decision Support System application using the Profile Matching method. With this designed system, it is hoped that it can help the Padang Ministry of Health Polytechnic to make decisions in determining outstanding students with predetermined criteria and values. The final score obtained from this study was 4.55 by Mutiara Mawaddah Anandri. So the results of the analysis are expected to be able to help the Health Polytechnic of the Padang Ministry of Health in determining outstanding students.